How do management decisions impact butterfly assemblages in smallholding oil palm plantations in Peninsular Malaysia? - Harianja, Martina F.; Stone, Jake; Mamat, Wan Z. W.; Hadi, Muhamad A.; Luke, Sarah H.; Azhar, Badrul; Turner, Edgar C. (John Wiley and Sons, 2024)
In the world's leading palm oil-producing countries (Indonesia and Malaysia), smallholders make up about 40 per cent of total oil palm plantation area. Management in smallholdings can be highly variable, ranging from intensive monoculture to polyculture systems, especially in the earlier years of cultivation when open canopies allow a variety of understorey crop types to be grown alongside oil palm. Currently, many plantations in the region are mature and due to be replanted, which is likely to have substantial impacts on the ecosystems within them, but studies investigating the impacts of alternative post-replanting management strategies in smallholder plantations are lacking. We investigated the impacts of replanting and choice of crop management following replanting (growing oil palm as a monoculture or polyculture) on habitat structure and complexity, and on the abundance, richness and composition of butterfly assemblages in smallholding oil palm plantations in Banting, Selangor, Malaysia. We also assessed the direct effects of habitat structure and complexity on butterfly assemblages. Butterflies are likely to be a valuable indicator group for monitoring the impacts of management practices on biodiversity as butterfly species also show a range of sensitivities to habitat disturbance, with some being vulnerable to change, but others being common in plantations. They are also a functionally important group that pollinate wild plants, are prey for larger species and are common in tropical systems. Across 27 plantations, we recorded 1227 butterflies from 5 families, 46 genera and 56 species. Habitat structure and complexity differed between management decisions (mature monoculture, immature monoculture, immature polyculture), although many environmental parameters overlapped. We found no significant differences in species richness, density and assemblage composition of butterflies between management decisions. However, changes in local environmental conditions, such as an increase in the coverage of understorey vegetation, increased the abundance of butterflies. Synthesis and applications. Our findings suggest that replanting oil palm and choice of mono or polyculture have relatively few effects on butterflies, but management for specific features in plantations could benefit butterfly assemblages. © 2024 The Authors. Journal of Applied Ecology published by John Wiley & Sons Ltd on behalf of British Ecological Society.